2016
DOI: 10.1192/bjpo.bp.115.001685
|View full text |Cite
|
Sign up to set email alerts
|

Case finding and screening clinical utility of the Patient Health Questionnaire (PHQ-9 and PHQ-2) for depression in primary care: a diagnostic meta-analysis of 40 studies

Abstract: BackgroundThe Patient Health Questionnaire (PHQ) is the most commonly used measure to screen for depression in primary care but there is still lack of clarity about its accuracy and optimal scoring method.AimsTo determine via meta-analysis the diagnostic accuracy of the PHQ-9-linear, PHQ-9-algorithm and PHQ-2 questions to detect major depressive disorder (MDD) among adults.MethodWe systematically searched major electronic databases from inception until June 2015. Articles were included that reported the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
195
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(210 citation statements)
references
References 63 publications
8
195
2
5
Order By: Relevance
“…70,71 Estimates of sensitivity, specificity, and NPV for the BDI-II from studies included in this review are in line with those found in other studies, 72 with PPV estimates from included studies in this review near the lower range but generally consistent with PPV estimates produced in other medical samples. The GDS, HADS, and PHQ did not have uniform versions (i.e., they differed in either items assessed or cutpoint used) employed in more than two studies in the present review, limiting comparability with other research, though in general the reported metrics from presently included studies appear broadly consistent with those reported from studies that have examined these measures in other non-post-ACS populations.…”
Section: Depression Screening Properties In Post-acs Patientssupporting
confidence: 88%
“…70,71 Estimates of sensitivity, specificity, and NPV for the BDI-II from studies included in this review are in line with those found in other studies, 72 with PPV estimates from included studies in this review near the lower range but generally consistent with PPV estimates produced in other medical samples. The GDS, HADS, and PHQ did not have uniform versions (i.e., they differed in either items assessed or cutpoint used) employed in more than two studies in the present review, limiting comparability with other research, though in general the reported metrics from presently included studies appear broadly consistent with those reported from studies that have examined these measures in other non-post-ACS populations.…”
Section: Depression Screening Properties In Post-acs Patientssupporting
confidence: 88%
“…Our PHQ-9 and PHQ-2 questionnaires were modified after feedback from members of the Amish community, and thus, the scores and thresholds on those questionnaires cannot be directly used to estimate diagnosis in the absence of thorough validation. Under any circumstances, meta-analyses have reported that both PHQ-9 and PHQ-2 scales cannot be used to clinically diagnose depression but they are useful for screening and referral for further clinical evaluation [37, 38]. …”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires also asked if the participant had experienced either of these feelings in the past. Studies have reported that PHQ-9 has a sensitivity ranging from 80% to 81.3% and specificity ranging from 85.3% to 92% [37, 38] and the PHQ-2 sensitivity ranges from 83% to 89.3% and its specificity ranges from 75.9% to 92% [36, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…The PHQ‐9 questionnaire is commonly used to screen patients for depression . It is composed of 9 items that are designed to check the symptoms of major depressive disorder as defined in the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐IV) .…”
Section: Methodsmentioning
confidence: 99%
“…In a systematic review of the psychological problems of cancer patients, the National Comprehensive Cancer Network recommended routine screening for distress, including depression . Distress among these patients is commonly assessed using the distress thermometer or the Patient Health Questionnaire‐9 (PHQ‐9) . Actually, the implementation of referral systems incorporating a screening tool produces several positive outcomes, such as reduced depression, increased doctor‐to‐patient communication, and the facilitation of referrals to a psycho‐oncology service …”
Section: Introductionmentioning
confidence: 99%